2011
DOI: 10.1002/jobm.201100365
|View full text |Cite
|
Sign up to set email alerts
|

Apa is a trimeric autotransporter adhesin of Actinobacillus pleuropneumoniae responsible for autoagglutination and host cell adherence

Abstract: Actinobacillus pleuropneumoniae is the causative agent of porcine pleuropneumonia, and adherence to host cells is a key step in the pathogenic process. Although trimeric autotransporter adhesins (TAAs) were identified in many pathogenic bacteria in recent years, none in A. pleuropneumoniae have been characterized. In this study, we identified a TAA from A. pleuropneumoniae, Apa, and characterized the contribution of its amino acid residues to the adhesion process. Sequence analysis of the C-terminal amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
(42 reference statements)
0
14
0
Order By: Relevance
“…The E. coli expression system provides an inexpensive way to produce glycosylated adhesins for diagnostics or vaccination purposes. The autotransporter adhesins of A. pleuropneumoniae mediate adhesion to the host cells and are therefore crucial for colonization and pathogenesis (38). All sequenced strains of A. pleuropneumoniae as well as a number of other pathogenic Pasteurellaceae species (such as H. influenzae or M. haemolytica), carry genes encoding a cytoplasmic glycosylation system.…”
Section: Discussionmentioning
confidence: 99%
“…The E. coli expression system provides an inexpensive way to produce glycosylated adhesins for diagnostics or vaccination purposes. The autotransporter adhesins of A. pleuropneumoniae mediate adhesion to the host cells and are therefore crucial for colonization and pathogenesis (38). All sequenced strains of A. pleuropneumoniae as well as a number of other pathogenic Pasteurellaceae species (such as H. influenzae or M. haemolytica), carry genes encoding a cytoplasmic glycosylation system.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many TAAs have been further identified, such as BtaE of Brucella spp. (18), Apa of Actinobacillus pleuropneumoniae (19), and EibD of Escherichia coli (20). Ata of Acinetobacter baumannii is involved in nosocomial infection (21).…”
mentioning
confidence: 99%
“…TAAs have attracted significant attention since their discovery on the Y. enterocolitica surface. In addition to YadA, Hia and Hif, recent studies have suggested that several additional life-threatening infectious Gram-negative bacteria possess one or more TAAs; these proteins include Apa from Actinobacillus pleuropneumoniae (Xiao et al 2012), SadA from Salmonella enterica (Raghunathan et al 2011), BpaA from Burkholderia pseudomallei (Edwards et al 2010), BadA from Bartonella (Riess et al 2004;, EmaA from Actinobacillus actinomycetemcomitans (Mintz 2004), and Cha from Haemophilus (Sheets et al 2008).…”
Section: Introductionmentioning
confidence: 99%